Analytically comparing disaster resilience across multiple dimensions. (March 2020) - Zobel, Christopher W.; Baghersad, Milad
Abstract: It is important to compare the resilience of complex human systems to different types of disasters, in order to assess their inherent vulnerabilities and take appropriate actions to strengthen them. Resilient behavior can be complicated and multi-dimensional, however, and one must be able to characterize the different ways in which that resilience actually exhibits itself in practice. With this in mind, this paper discusses creating a multi-dimensional indicator for the resilience of a complex human system, and it explores an approach for visualizing and analyzing the relationships between each of the individual resilience dimensions. Because decision makers may differ on the relative contribution of the different dimensions to overall resilience, the paper further discusses the issue of weighting the different dimension values and the impacts that such a weighting scheme can have on the relative ranking of different scenarios. We illustrate the ability to characterize the complexity of multi-dimensional resilience by analyzing an empirical data set that measures the relative resilience of the New York metropolitan area to seven different natural disasters between 2010 and 2012. Highlights: Disaster resilience is complex and multi-dimensional in nature. Visualization of the different characteristics of disaster resilience can help with understanding this complexity. Quantitative approaches for characterizing multi-dimensional resilience are necessary in order to compare the relative effectiveness of different resilience strategies. This paper therefore presents a new, quantitative approach for visualizing and analyzing disaster resilience. The approach is illustrated with an empirical data set that captures different aspects of resilient behavior in New York City across several different natural disasters between 2010 and 2012.